Correlation between microstructural characteristics from micro-CT of foamed concrete and mechanical behaviors evaluated by experiments and simulations - Kim, Ji-Su; Chung, Sang-Yeop; Han, Tong-Seok; Stephan, Dietmar; Elrahman, Mohamed Abd (Cement & concrete composites, 2020)
Microstructural characteristics and properties of foamed concrete, a cellular lightweight cement paste with entrained air voids, are investigated. The complex 3D microstructures of the foamed concrete with different densities are obtained by micro-CT imaging and binarized as two-phase (pore/solid) materials by image processing. The mechanical responses of the microstructures are evaluated by simulations within the phase-field fracture model, and the input material parameters for simulations are identified. Microstructural characteristics and properties from experiments and simulations are correlated. In particular, linear attenuation coefficients for the solid phase in micro-CT images correlate with input material parameters. These correlations can serve to determine solid-phase input material parameters in foamed concretes with different densities. The behavior of foamed-concrete binders, modeled as multi-phase solids, should thus be evaluated more accurately through simulations, based on the observed correlations.